El «Tirant lo Blanch» i les seues traduccions anteriors al segle XIX: aspectes de recepció i de traducció - Martines, Vicent (Caplletra. Revista Internacional de Filologia, 1997)
On the basis of the premise that every translation is a recreation to a great extent, the author studies the translations of Tirant lo Blanch into Castilian, Italian and French made before the XIXth century. By means of the comparison of texts and the analysis of quotations, notations and, in general, all the difficulties found in the different manuscripts where these translations are kept, Vicent Martines elaborates a history of the reception by these three cultures of the Valencian novel. Through this history we can find out that Tirant lo Blanch was not very different from a chivalresque book of this period (as regards the typographic solutions, the format and the publishers' and translators' remarks) and that it was interpreted as a real chivalresque manual.